2019
DOI: 10.1051/0004-6361/201936061
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of terrestrial planets and water delivery in the habitable zone using N-body simulations with fragmentation

Abstract: Aims. The goal of this research is to study how the fragmentation of planetary embryos can affect the physical and dynamical properties of terrestrial planets around solar-type stars. Our study focuses on the formation and evolution of planets and water delivery in the habitable zone (HZ). We distinguish class A and class B HZ planets, which have an accretion seed initially located inside and beyond the snow line, respectively. Methods. We develop an N-body integrator that incorporates fragmentation and hit-an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
2
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(39 citation statements)
references
References 45 publications
3
32
2
2
Order By: Relevance
“…The authors compared two sets of identical initial conditions and performed a series of N-body simulations with and without fragmentation. The results derived in Dugaro et al (2019) are consistent with those obtained by Chambers (2013) and Genda et al (2012).…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…The authors compared two sets of identical initial conditions and performed a series of N-body simulations with and without fragmentation. The results derived in Dugaro et al (2019) are consistent with those obtained by Chambers (2013) and Genda et al (2012).…”
Section: Introductionsupporting
confidence: 90%
“…Recently, in Dugaro et al (2019), we presented an N-body code called D3 that allows planetary fragmentation for gravitydomain bodies based on the works of Chambers (1999Chambers ( , 2013, Leinhardt & Stewart (2012), Genda et al (2012), andMustill et al (2018). The authors studied terrestrial planet formation on a protoplanetary disk, hosted by a solar-type star, and the presence of Jupiter and Saturn analogs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with our results, that study found that most Mars analogs accrete more slowly than the exponential growth curve of Dauphas & Pourmand (2011) and proposed various dynamical methods to make them grow more quickly. These include the implementation of non-perfect merging between colliding protoplanets, an effect which slightly prolongs Earth's accretion (e.g., Chambers, 2013;Dwyer et al, 2015) but could potentially form Mars more quickly via fragmentation (Kobayashi & Dauphas, 2013;Dugaro et al, 2019). N-body studies of "pebble accretion" disagree on whether that regime promotes (Levison et al, 2015;Matsumura et al, 2017) or discourages (Voelkel et al, 2021) the formation of small terrestrial planets.…”
Section: Other N-body Approachesmentioning
confidence: 99%
“…Such interactions produce orbits that cross each other, which results in successively close encounters between them which, in turn, lead to collisions among them, ejections from the system, and collisions with the central star. Several works have shown that collisions between gravity-domained bodies yield different outcomes depending on the target size, projectile size, impact velocity, and impact angle (Leinhardt & Stewart 2012;Chambers 2013;Quintana et al 2016;Dugaro et al 2019). In the present study, all collisions were treated as perfect mergers, conserving the total mass of the interacting bodies in each impact event.…”
Section: N-body Experiments: Characterisation Parameters and Initial Conditionsmentioning
confidence: 99%